Efek Moderasi Pelaporan Berkerlanjutan dalam Pengaruh Praktik Penghindaran Pajak Terhadap Nilai Perusahaan : Indonesia - Jecky; Suparman, Meiliana (Jurusan Akuntansi Politeknik Negeri Padang, 2021)
Researches on tax avoidance practices and firm value are still inconclusive. Therefore, this study examined whether sustainability reporting moderates the effects of tax avoidance on firm value. Tax avoidance is measured by pull effective tax rates (PETR) and cash effective tax rate (CETR). PETR is a measurement of the value of income that is taxed, while CETR is a measurement of taxes that are actually paid. The study used secondary data taken from companies listed on the Indonesia Stock Exchange from 2016 to 2020. Hypotheses testing using panel regression method. Based on the examination of 1,374 observations, it was found that only 12.7% of the sample prepared sustainability report. It shows that sustainability reporting is still not mandatory for many public companies in Indonesia. According to the hypotheses test, tax avoidance (PETR or CETR) does not affect firm value. Sustainability reporting has a negative moderating effect but not significantly. On the other hand, firm value is significantly influenced by several control variables, including size, profitability, leverage, and age of the firm. These findings complement the literature on the role of sustainability reporting publications in determining firm value in relation to tax avoidance practices. Furthermore, this study is expected to increase the motivation of Indonesian listed companies to produce sustainability reports.